Análise de patentes sobre sistemas de colheita de cana-de-açúcar - Pinto, Márcia Ferreira (2010)
Either by environmental, economical, technological or social reasons, the total mechanization of field operations in the cultivation of sugar cane has already been a reality in the sugar cane plantations in Sao Paulo state in which the harvesting operations (mainly cuts) performed by the man beforehand are being systematically replaced by machines, trying to match productivity with sustainability and the development of the field and the city. Within this scenario, the market for machinery and agricultural implements for the harvesting of the sugar cane has grown, but some technological barriers have been identified as effective for the advancement of the mechanization in the harvest of sugar cane: 1) the cleaning system of stems that according to experts, does not promote an efficient cleaning, taking to the plant impurities that compromise the production, 2) the size of the machines, which does not meet the needs of the small and medium producers (the biggest number in the country), 3) a decrease in the weight of the machines, trying to reduce the soil compaction; 4) harvest in several rows (today the harvest is done in the most two rows) to reduce costs of the operation. This work is a result of the research in patent documents to know and to prospect the current state of technological systems for collection, focusing mainly the system of mechanized harvesting of sugar cane and especially the sub-cutting system, building technological indicators to contribute with the advancement of the set of solutions for the accomplishment of the agricultural harvest of the cane. The methodology used in this work was the bibliography in patent documents, in the database Derwent Innovations Index. It was developed using a search expression CIP and the keywords to limit the universe of research in which 587 patent records deemed as relevant were recovered. After processing the data in Infotrans, they were treated with the VantagePoint software which crossed the data and created thesaurus, allowing some inferences. The results identified some scenarios that show the boundaries of the technology in harvesting the sugar cane. It was also possible to identify the countries and the companies that place more patents, and to identify which countries have been trying to use the technology for the mechanization of the harvest. An example is China with a significant participation since 2005 in number of applications for patents. Therefore, it was possible to draw some scenarios that are best explained in Chapter 4: relating to the results achieved.